Geogenic Arsenic and Microbial Contamination in Drinking Water Sources: Exposure Risks to the Coastal Population in Bangladesh - Saha, Ratnajit; Dey, Nepal C.; Rahman, Mahfuzar; Bhattacharya, Prosun; Rabbani, Golam H. (Frontiers in Environmental Science, 2019)
The study aimed to investigate the most usable drinking water sources quality and the dependent population’s exposure to potentially contaminated water. The specific area chosen for the study was the coastal area in Satkhira district’s Tala Upazila. 649 most usable drinking water sources were selected that included Deep Tubewell (DTW), Shallow Tubewell (STW) and Pond Sand Filter (PSF) for drinking water sampling. Following standard sampling procedures, in-situ measurements were taken for seven important water quality parameters: Arsenic-As, Iron-Fe, Electrical Conductivity-EC, Temperature-Temp, Total Coliform- TC, E-coli and Fecal Coliform-FC. In addition, semi-structured questionnaire surveys were conducted at corresponding dependent households (HH). Weighted arithmetic water quality index (WQI) was used to calculate the suitability of the derived water for drinking purposes. In the tested water sources, As, Fe and EC range were found 0-500 µg/L, 0-18 mg/L and 165-8715 µS/cm, respectively. Of all tested water sources, 74% exceeded permissible limit for As, 83% for Fe and 99% for EC, according to WHO standards. Comparatively higher percentage of Point of Uses (PoU) were found to be more contaminated than Point of Sources (PoS) such as TC found in 38% PoS and 54% of corresponding PoU, E.coli found in 24% PoS and 35% of PoU and FC found in 45% PoS and 55% of PoU. WQI suggested that the majority (72%) of most usable drinking water sources were found to be unsuitable for drinking. Thus, 40% of the population (0.12 million) in the study area were directly consuming contaminated water, dependent household members most frequently suffered from fever, diarrhea and high blood pressure, resulting in the average household to spend USD 3-13 per month/HH for health-related expenditures, which is higher than national average. To acquire safe drinking water, the majority (58%) of the dependent HH expressed willingness to pay USD 1 per month/ HH which is costly for them. The situation can be improved by installing deep tube well for safe drinking water, periodically testing of the water quality, educating public for better hygiene practices, and providing entrepreneurial incentives to help deliver safe water to the public at lower cost.